Projection range of eDNA analysis in marshes: A suggestion from the Siberian salamander (Salamandrella keyserlingii) inhabiting the Kushiro marsh, Japan - Daiki Takeshita (2020)
© 2020 Takeshita et al. Background: Freshwater ecosystems are rapidly declining. The Siberian salamander (Salamandrella keyserlingii) which inhabits the Kushiro marsh in Hokkaido, Japan has lost some habitat due to human activity. There are many challenges associated with conventional monitoring methods, including cost, the need for specialist personnel, environmental impact, and ability to detect the presence of this species; thus, we investigated the feasibility of using environmental DNA (eDNA) analysis to detect its presence and identify its breeding grounds. Methods: We performed tank experiments to confirm eDNA emission from egg sacs, larvae, and adult Siberian salamanders in the water. We also performed water sampling and visual observation of egg sacs in the Kushiro marsh during the end of the breeding season and the larval season. Results: The tank experiments found eDNA emission from all growth stages. It also implied concentrated emissions just after spawning and after hatching, and limited emissions during the incubation phase in egg sacs. We also detected eDNA in the field, likely reflecting the distribution of egg sacs or larvae. Combining this data with visual observations, it was determined that the eDNA results from the field were best explained by the number of egg sacs within 7-10 m of the sampling point. Conclusions: The results of this investigation show that the breeding sites and habitats of marshland species can successfully be monitored using eDNA analysis. They also suggest that the eDNA results from the marshes may reflect the biomass that is in close range to the sampling point. These results support the increased use of eDNA analysis in marshes and provide knowledge that could improve the interpretation of future results.